Successful early use of anti-SARS-CoV-2 monoclonal neutralizing antibodies in SARS-CoV-2 infected hematological patients - A Czech multicenter experience - Weinbergerová, Barbora; Demel, Ivo; Víšek, Benjamin; Válka, Jan; Čerňan, Martin; Jindra, Pavel; Novák, Jan; Stejskal, Lukáš; Kovácsová, Flóra; Kabut, Tomáš; Szotkowski, Tomáš; Hájek, Roman; et al. (Hematological oncology, 2022)
COVID-19 significantly impairs survival rates among hematological patients when compared to the general population. Our prospective multicentre project analyzed early administration of anti-SARS-CoV-2 spike protein neutralizing monoclonal antibodies (NmAbs) - bamlanivimab (72%) and casirivimab/imdevimab (28%) - efficacy among hematological patients with early-stage COVID-19. Mortality rate was compared to a control cohort of 575 SARS-CoV-2 positive hematological patients untreated with any specific anti-COVID-19 therapy. 88 hematological patients with lymphomas, acute leukemias, and myeloma as their most frequent underlying diagnoses (72%) were evaluated with a 97 days median follow-up after NmAb administration. One third of patients (32%) were treated with an anti-CD20 monoclonal antibody before COVID-19 diagnosis. Median time between first COVID-19 symptom and NmAb administration was 2 days. When administering NmAb, 29%, 57%, 11%, 2%, and 1% of our patients had asymptomatic, mild, moderate, severe, and critical degrees of COVID-19, respectively. 80% of baseline asymptomatic patients remained asymptomatic following NmAb administration. Median duration of COVID-19 symptoms after NmAb administration was 2.5 days. Progression to severe/critical COVID-19 occurred among a total of 17% (15/88) of our cases and numerically higher with bamlanivimab versus casirivimab/imdevimab (21% vs. 8%; p = 0.215), and myelomas (29%), lymphomas (17%) and acute leukemias (18%), respectively. During final follow-up, nine deaths (10%) were recorded - all after bamlanivimab (p = 0.056) with 8% attributed to COVID-19. Regarding "remdesivir/convalescent plasma naïve" patients, COVID-19 mortality rates were significantly lower in our NmAbs treated cohort compared to the control cohort of untreated SARS-CoV-2 positive hematological patients (6% vs. 16%, p = 0.020), respectively. Our study validated the safety and efficacy of NmAbs early use among hematological patients with newly diagnosed early-stage COVID-19 in terms of alleviating infection course and decreasing mortality. Results confirmed a more positive effect of a casirivimab/imdevimab combination versus bamlanivimab monotherapy.
Keywords: neutralizující protilátky; testování na COVID-19; Immunization, Passive; SARS-CoV-2; Česká republika; casirivimab; COVID-19; Prospective Studies; Czech Republic; hematological malignancy; bamlanivimab; Antibodies, Neutralizing; sérologická léčba covidu-19; COVID-19 Testing; COVID-19 Serotherapy; Humans; prospektivní studie; COVID-19 Drug Treatment; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; imdevimab; pasivní imunizace; farmakoterapie COVID-19; anti-SARS-CoV-2 monoclonal neutralizing antibodies; lidé